A leap of faith? Trust in the police among immigrants in England and Wales - Bradford, B; Sargeant, E; Murphy, K; Jackson, J (Oxford University Press, 2015)
It is often assumed that immigrants in countries such as the United Kingdom will report lower levels of trust in the police. Immigrant communities are thought ‘difficult to police’, and minority groups frequently experience problematic relationships with police. Yet, there has been little empirical investigation of this issue in the United Kingdom. In this paper, data from the Crime Survey of England and Wales are used to explore the relationship between immigration and trust in the police. Results suggest that trust is higher among immigrants than among the UK-born population, although there is important variation by time since arrival and experience of policing. Trust in the police is also higher in neighbourhoods that have more immigrants. The paper concludes with some reflection on the nature of trust in the police.